Domestic Violence in Danielle Steel's Journey (A Liberal Feminism Approach) - ARYANI FITRI HIRA KARTIKA (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
Domestic Violence in Danielle Steel's Journey (A Liberal Feminism Approach) Aryani Fitri Hira Kartika English Department, Faculty of Languages and Arts, Surabaya State University Aryanifitri11@gmail.com Fabiola Dharmawati Kurnia English Department, Faculty of Languages and Arts, Surabaya State University fabkurnia@gmail.com Abstrak Permasalahan kekerasan dalam rumah tangga selalu menjadi ancaman bagi wanita. Hak asasi manusia mereka ditiadakan oleh suami.Tujuan penelitian ini adalah menganalisis bagaimana kekerasan dalam rumah tangga dan bagaimana wanita melawan kekerasan yang tergambarkan pada Journey karya Danielle Steel. Penelitian ini menggunakan metode data deskriptif-qualitatif dengan pendekatan konsep kekerasan menurut Paula and Margie untuk menunjukkan bentuk kekerasan dalam rumah tangga dan liberal feminisme menurut Naomi Wolf dan John Stuart Mill untuk menunjukkan usaha wanita untuk melawan kekerasan dan bangkit dari permasalahannya. Hasil penelitian ini mengungkapkan (1) bentuk kekerasan yang dialami Mddy, tokoh utama dalam Journey yang ditinjau dari pendekatan liberal feminisme adalah kekerasan emosional; penghinaan, ancaman, menganggap rendah, dan pengisolasian sosial, sementara kekerasan seksual;pemaksaan seks, pemaksaan sterilisasi, penyiksaan secara seksual, dan menganggap wanita sebagai objek seks. (2) Bagaimana Maddy melawan kekerasan melalui berani berbicara ketika Ia ingin diberi kesempatan untuk memberi ide-idenya dalam area pekerjaan, membuat keputusan dalam hidupnya, bersosialisasi dengan teman-temannya, melalui tindakan ketika Ia menentang perintah suaminya untuk menjauhi anak istrinya, keinginan Maddy tetap pada merawat anaknya, dan yang terakhir melalui personal autonomi ketika Ia mengambil sikap untuk berpisah dari suaminya demi terbebas dari kekerasan suaminya. Berpisah dari suaminya, Ia bisa hidup mandiri tanpa bayang-bayang suaminya. Keywords : Kekerasan, Wanita, Perlawanan, Liberal Feminisme Abstract Violence always becomes threat for women. Their human rights are denied by their husband.The purpose of this study is analyzing how domestic violence to woman and how woman resists against violence as reflected in Danielle Steel’s JOURNEY. This research of method used to analyze the data is a descriptive-qualitative with an approach of domestic violence by Paula and Margie to show the forms of domestic violence and liberal feminism by Naomi Wolf and John Stuart Mill to show her efforts to resist against violence and revival from her problems. The result of this research exposes that (1) violence experienced by Maddy as the main female character are emotional abuse; humiliation, threats, belittling, and social isolation, meanwhile sexual abuse; rape, enforced sterilization, torturing sexually, and looking woman as sexual object. (2) How Maddy resists against violence through speak out as she wants to be given opportunity in giving her ideas in her working place, making her own decisions in her life, socializing with her friends, and, through doing action as Maddy tries to oppose every her husband’s commands, one of them is her decision for taking care her children and through being personal autonomy when she decides to divorce with her husband and lived independent with working without the shadows of her husband. She has had power to be personal hood in determining self, mind, body, and feeling that divorce is the best way for sake of happiness and pleasure (freedom of emotional and sexual abuses) perpetuated by her husband. Keywords : Violence, Women, Resistance, Liberal Feminism INTRODUCTION: God creates a man to the earth for living in love with others but in reality lately the acts of violence has always been part of the human experience. Acts of violence can happen in everywhere, be experienced by anyone, and be perpetrated by anyone (Dustin, 2009:87). However, survey from UNICEF Research Centre in 2000 states that violence is regular part of women’s experience in domestic violence. They are unable to make their own decisions, voice their own opinions or protect themselves and their children for fear of further repercussions. Their human rights are denied and their lives are stolen from the abuser by regularly getting threats of violence (Khan, 2000:2). Many factors make women experience violence, one of them is gender bias, unequal power relations between men and women in which women is forced into a subordination position compared women than men that leads women as the victim of men dominance and discrimination and to prevention of the full advancement of women (Khan, 2000:2). Violence in domestic life always happens toward wife as a party who is regarded weaker than her husband. Joda et al, 2009:2 states that husband often do not feel guilty with what he does even he feels no breaking the law when he commits violence to his wife. Some women activists believes that violence in domestic sphere is rooted in belief of patriarchal system that still applied by husband in system of his household. According to Dobash, patriarchy contributes toward wife abuse. The system had defined the differences of gender between men and women. Husband was supposed to be strong, dominant, authoritarian, aggressive, and rational provider while women had devalued as secondary and inferior who had been assigned to be irrational, dependent, passive, submissive, soft, nurturing (in Margie, 2002:34). Patriarchal society regarded women as men’s property and gave authority toward husband to control and decide decision for wife. Araji and Carlson (2001) argued that patriarchal societies may foster domestic violence because the dominant male is perceived to be appropriately disciplining and controlling the behaviour of the subordinate wife in the family (in Florence, 2008:592). The forms of women abuse can be classified into three forms, those are physical abuse, emotional abuse, and sexual abuse. Physical abuse is like grabbing, hitting, and kicking, sexual abuse is like demanding sex when one’s partner is unwilling, enforced to sterilization, regarding women as a sex object, and emotional abuse is like humiliation, threatening, belittling, and social abuse (Paula, 2006:5 &16 and Margie, 2000: 3-6). Bhasin states that patriarchy as a concept to refer social system of masculine domination over women. Patriarchal society places men in superior or masculine position meanwhile women is put in subordinate position (2000:10). Murniati states that patriarchy is a system of socio-culture that marginalizes women’s position in all aspects including in economic, social, education, politic sphere as if the system legitimizes some a various inequality, deprivation, and oppression over women (2004:227-229). In patriarchal situation, women had only little influences in society where they did not have rights on common areas in society such as in family, social, government, education. So, women’s economic social, political, psychological condition depended on men. Domestic violence always becomes the hidden issue. Almost all of the victims are unwilling to report the police because wife still depends on financial on husband, wife still loves her husband, and many reason else. Summer states that many the victim is always silent toward violence perpetrated by her husband, never resists the abuser and never tells anyone (Summers, 2002:170). Moreover, according to Joyce, victims of violence over time experiences more serious consequences than of one-time incidents. Domestic violence against women where husband as the perpetrator can lead psychological consequences for the victim (2009:134-135). Gender bias that causes women are always marginalized, subordinated, and oppressed in the family at the place of work, and in society emmerges feminism. Feminism is an awareness of women oppression at the place of work within the family and an awareness of patriarchal control (Bhasin, 2000:31). Meanwhile Carter states that feminism is a movement for women that attempts to resist the dominance of a patriarchal society have a long history (2006:910). One of feminism movement that defend equality rights between men and women is liberal feminism. Liberal feminism is a movement that is reflected in every struggle done by women to demand the right of freedom (Humm, 2002:250). Liberal feminism emphasizes the importance of individualism, freedom, especially freedom of choice. The feminist movement is that women gain control. Both of the body itself as well as the social world. They reject the gender symbols attached to each sex and gender socialization to children that had been done. Women experience discrimination because of gender inequality but women should have same opportunity like men in all of aspects, including private field, or public field, or public field (Ritzer, 1992:450). John Stuart Mill states that women must be personal autonomy as women are rational beings and have the same capacity as men. Problems faced by women more often caused by women if legal reform has happened to make equality between men and women (Tong, 2009:29). Women who success financially comfortable, succesful does not guarantee them will freedom from discrimination and violation. As women regard themselves as the victim of discrimination and violation, Wolf states that women have the power to control what happens to them so stop thinking of themselves as victim and to capitalize on the power inherent in their majority status. Society does not oppress them. It is time for women to do self defeating (speak out) against violation and discrimination. Proclaiming themselves as victimhood does not project strength (Wood, 2009:84). Journey is a novel that will be analyzed. This research chooses the novel as the main female character, experiences violence emotionally and sexually during her marriage life however Maddy is a representation of woman’s movement who is brave to speak out against violence perpetruated by her husband but she never tries to hate marriage institution. Maddy as a woman who is not afraid to out of comfort zone and false happiness created by her husband after getting supports from her friends, a support group for battered women, daughter. She escapes from the shackle of oppression to be an independent, free women with her daughter and her friends who support her not like many wives commonly are afraid to escape from violence or say divorce cause they still depend on their husband. Based on the explanation above, the writer is interested to analyze how domestic violence is reflected using the concept of domestic violence from sociological approach by Paula and Margie and how woman resists against violence and revival from her problems by using liberal feminism by Naomi Wolf and John Stuart Mill. Theoritical Framework In producing a good understanding of the conflicts in domestic life which woman experiences and how woman resists against violence in Danielle Steel’s Journey, this study applies extrinsic approach in analyzing the problems. The theory of domestic violence by Paula and Margi is chosen as the tool to find out domestic violence to woman is reflected in Danielle Steel’s Journey. Theory of domestic violence is a theory which is used to analyze how the forms of abuses which is experienced by the victim. The types of domestic violence according to Paula and Margie consist of physical abuse, emotional abuse, and sexual abuse. (1) Physical abuse is the action of physically assaults, causing injury, pinching, or squeezing, (2) emotional or psychological abuse is consistently doing or saying things verbally that results in fear, loss of confidence, loss of the ability to act, a sense of helplessness and or severe psychological suffering on a person, and (3) sexual abuse is including sadism and forcing a person to have sex when he or she does not want to, forcing a person to engage in sexual act that he or she does not like or finds unpleasant, frightening, or violent, touches the victim sexually in uncomfortable ways, and regards women as a sexual object. Liberal feminism is chosen as the tool to analyze how woman resist against violence. Its feminism emphasizes that violence toward women is based on unequal power relations between women and men. Its theory emphasizes equal individual rights and liberties for women and downplaying sexual differences. Liberal feminist propose a series of strategies for eliminating gender inequality; supporting individual in challenging sexism wherever it is enccountered in daily life without hating the marriage institution. As women experience inequality, the soulution is on women themselves (Ritzer, 1992:452-53). In challenging discrimination and violation toward women, Wolf demands woman to do self defeating (speak out). Its concept is used by Wolf to give powerness for women resist against discrimination and violation (Wood, 84). Wolf states that women are not needed to ask for permission toward anyone for achieving social equality (1999:79). Meanwhile John Stuart Mill gives powerness on women for being personal autonomy. Personal autonomy is a autonomous decision making. John Stuart Mill states that women have powerness as personhood over their self, their thinking, their feeling, their body in determining a choice in their living for sake of happiness and pleasure but not obstruct another people’s right in the process (Tong, 2009:16) Based on the background of the study above, the questions below will be answered. (1). How is domestic violence to woman reflected in the Danielle Steel’s Journey? (2). How does woman in Danielle Steel’s Journey resist against violence? Research Design and Method: To analyze Danielle Steel’s Journey, this study uses descriptive qualitative. Thomas (2003) defines qualitative methods as method that involves research by describing kinds of characteristics people and events without comparing the events in term of amounts. The main data is the novel entitled Journey by Danielle Steel, published in 2000 by Dell Publishing, New York. Meanwhile the additional data are taken from many sources such as journal, book, and internet sources. Besides that, quotations in the novel is taken also related how domestic violence to woman is reflected and how woman resists against woman as represented by the main female character of Maddy. There were some steps taken in conducting this study. First, reading was the first step to do to gain the idea the novel intends to deliver. After the writer has finished reading the novel, the next step which was hold was close reading. This step was applied to find quotations related to the topic and problems going to analyze. Close reading was done three times. The first close reading was to find the quotations which are related how domestic violence to woman, then the second close reading was to find how woman resists against woman as represented in Danielle Steel’s Journey. The data observed from the novel were then analyzed to the statement of the problems. It was then synchronized with the similar concept of domestic violence by Paula and Margie, concept of victimization by Joyce, and the concept of liberal feminism by Naomi Wolf and John Stuart Mill taken from journals, books, and critical essays. The synchronized data were useful to take final conclusions. Therefore, the significance of the study can be achieved well. Data analysis For the first question this study take theory from the theoritical framework which concerns with forms of abuse toward woman. The concept of domestic violence by Paula and Margie will be explained in this research to find out how domestic violence to woman is reflected in Danielle Steel’s Journey. In this research, the writer only found two forms of abuses to women, they are emotional abuses, and sexual abuses. For the second question this study take theory from the theoritical framework which concerns with women’s efforts to resist against violence. The concept of liberal feminism by Naomi Wolf and John Stuart Mill which are used to reveal how woman in Danielle Steel’s Journey resists against violence. RESULT (1). As the explanation of the domestic violence, this study finds out domestic violence to woman into two forms of abuse, they are emotional abuse and sexual abuse. Emotional Abuse consists of humiliation, threatening, belittling, social isolation. Meanwhile sexual abuse consist of rape, enforced sterilization, torturing sexually, and looking woman as a sexual object. (2). As the explanation of liberal feminism by Naomi Wolf and John Stuart Mill, this study reveal how woman resists against violence. The strategy of Maddy’s resistance to get out of domestic violence in Danielle Steel’s Journey through speak out, doing action, and being personal autonomy. 1.1 Emotional Abuse 1.1.1 Humiliation “I don't give a damn what you think. I don't pay you to think. I pay you to look good and read the news of a TelePrompTer. That's all I want from you. And with that, he walked into his bathroom, and slammed the door behind him, as she burst into tears in their bedroom. (Steel, p. 34) The quotation above show the form of humiliation by men toward women. In this Journey, Jack always puts his wife into subordinate position. Jack never regards his wife having capability in thinking. Jack just cares how Maddy could look beautiful in front of audiences without giving opportunity for her in giving her arguments or ideas as she is delivering the news. Jack will getting angry as Maddy tries to oppose his commands. One of his commands is prohibitting his wife to hold the program of editorial however Maddy still holds it for the sake of helping her new friend who committed suicide due to abused by her husband, Jack’s friend also. 1.1.2 Threatening “I heard you, she said numbly. And I hate you for it. I don't give a damn what you think or feel about this. I only care about what you do, and it goddamn better be the right thing this time, or you're finished. With me and the network. Is that clear, Mad? She looked at him for a long moment and then turned on her heel and walked swiftly down the stairs, back to her own floor. She was pale and shaking.” (Steel, p.63) The quotation above shows that Jack always tries threats for Maddy, his wife. Besides she will loss her jobs, Jack will divorce Maddy as his threat for his wife as she does not obey what Jack says to her. Maddy loves so much her husband and also depend financially with her husband. That’s Maddy has no other alternatives to leave her husband. In her marriage, Maddy has no power over her husband. Jack always regards her as his property that could be ordered by Jack. Jack feels Maddy as his wife and his employee so he deserves to control his wife as she tries to show her potential in giving comments which acrosses with Jack’s principles. 1.1.3 Belittling “That's insulting! It's the truth. As I recall, Mad, you never went to college. In fact, I'm not even sure if you finished high school. It was the ultimate put-down, insinuating that she was too stupid and uneducated to think (Steel, p. 90) The quotation above shows that Maddy tries to oppose all of belittling which is perpetruated by Jack to her however Jack gives awareness to Maddy that the reason of belittling is because Jack doubts whether Maddy ever finished her school or not. The unequal power relation in educational things lead discrimination over Maddy by Jack. Jack belittles Maddy as a stupid wife so Maddy should put down with her husband’s commands. 1.1.4 Social Isolation “She didn't have that many friends in Washington, she'd never had time to make them and those she had made, Jack never liked, and eventually pressured her not to see them. She never objected because Jack always had some objection to them, regarding her friends were fat, ugly, inappropriate, or indiscreet. He kept Madeleine carefully guarded, and inadvertently isolated. She knew he meant well in protecting her, and she didn't mind, but it meant that the person she was closest to was Jack, and in recent years, Greg Morris.” (Steel, p. 25) From the quotation above, social isolation is as form of discrimination. Men have full power over women as well as limits women to socialize with their friends. In Journey, Jack as the head of family, he determines which is a friend should be and should not be met by Maddy. Meanwhile Jack is freedom to choose which a friend he wants to meet. Besides his bussiness relation, he can also meet with woman. The quotation can be seen below: “He had been so quick to explain the photograph of the woman he’s been with at Annabel’s in london (Steel, p.159) 1.2 Sexual Abuse 1.2.1 Rape “He was smiling at her, and he reached out a hand and gently touched her breast, and then before she could stop him, he had grabbed her so hard, it made her gasp, and she begged him to stop “Why, baby? Tell me why? Don't you love me? I love you, but you're hurting me. There were tears in her eyes as she said it. I don't want to make love tonight, she tried to say, but he didn't listen, he grabbed a handful of her hair and sharply pulled her head back. What she sensed most in his love for her was danger. (Steel, p.87) From the quotation above shows that Jack regards Maddy as his own property which could be used by Jack anytime Jack wants. Jack always controls Maddy’s sexuality. It can be shown from the quotation above as Jack always forces Maddy to have a sex with him although Maddy does not want to have a sex with Jack or finds unpleasant, frightening, violent when having a sex. Jack does not care with his wife’s refusal, instead Jack grabs a handful of her hair and sharply pulled her head back to make his sexual impulse satisfied. 1.1.5 Enforced Sterilization “Jack convinced Maddy that children will obstacle her career. Jack had made it very clear to her right from the beginning that he didn't want children. And after a brief period of mourning for the babies she would never have, at Jack's insistence, Maddy had had her tubes tied. It seemed easier to give in to Jack's wishes and not take any chances. He had given her so much, and wanted such great things for her. She could see his point that children would only be an obstacle she'd have to overcome, and a burden on her career. But there were still times when she regretted the irreversibility of her decision. (Steel, p. 15). From the quotation above shows forcing woman to tie the rope uterus shows the violations of human rights because it is band for woman’s reproduction where woman will never have children again. The factors that leads this abuse still attached to the dominant assumption has the right to control the weak and the wife playing the role of a person who is required to comply, in terms of the economic dependence of women makes women cannot do anything other than comply with applicable rules. Jack Maddy action to force the rope cut the uterus with the aim that Maddy is not hampered career is a form of self control female reproduction by males while liberal feminism oppose the restrictions on reproduction for having offspring is the right of every individual, and no one was allowed to prohibit or restrict. 1.1.6 Torturing sexually “Are you going to be a good girl now?” he asked, taunting her, torturing her with pleasure. “Do you promise?” “I promise,” she said breathlessly. “Promise again, Mad.” He was a master at what he was doing, it had taken long years of practice. “Promise me again“I promise I promise I promise I'll be good, I swear.” All she wanted now was to please him, and from the distance, she knew she hated herself for it. She had sold out to him again, given herself to him again, but he was too powerful a force to resist (Steel, p. 70) From the quotation above can be stated that Jack as a husband who tries to pressure toward his wife in order to always being submissive and does not break commands which have applied by her husband. Jack reminds his wife with torturing her sexually slow by slow when having sex, in order to his wife realizes that the acts which have been done by Maddy is wrong. As Maddy’s position is in inferior status and depends financially toward her husband, Jack regards her as his own property that can be treated anything. 1.1.7 Looking woman as a sexual abuse “They often lay there for a while before they went to sleep, talking about what had happened that day, the places they'd been, the people they'd met with, the parties they'd been to. As they did now, and Maddy tried to guess what the President was up to. I told you, I'll tell you when I can, stop guessing. Secrets drive me crazy, she giggled. You drive me crazy, he said, turning her gently toward him, and feeling the satin of her flesh beneath the silky nightgown (Steel, p. 15). The quotation above shows that woman still is put in inferior position. Because of her position in inferior, man always regards woman’s existence as a sexual object not as a friend in helping her husband in solving the problems. From the quotation above, Maddy feels curious what is talking with her husband with the president, she tries to ask well but her husband instead say crazy to Maddy. Jack only focuses on her body which is reflected in he stops her husband’s conversation which tries to ask what happens between her husband and president, Jack instead turns Maddy gently toward him, and feeling the satin of her flesh beneath the silky nightgown. 2. The Strategy woman’s resistance against violence 2.1 Speak out “Have you ripped Jack's head off yet about our editorials? He grinned at her. No, but I will later, when I see him. As Jack and Maddy sped together toward Georgetown, she said to Jack “What the hell happened to our editorials? “Bullshit, Jack, they love them. Whydidn't you say something to me about it this morning?” She still looked annoyed. You never even asked me. It would have been nice to know. I think you really made the wrong decision on that one. (Steel, chapt 3: 27) The quotation above shows that Maddy tries to do refusal against Jack’s treatment that suddenly stopped the editorial program which is hosted by Maddy. For Maddy, the act of Jack that has stopped the editorial program which is hosted by her is as form of individual rights violation as Jack who always created his own decisions without giving freedom his wife to speak or deliver her ideas or just giving refusal with Jack’s concepts which must be runned by his wife. In working place, Jack is as a concept maker meanwhile Maddy is just a puppet that only run the duties of work from Jack without being given the opportunity to give her ideas. Maddy dare to challenge Jack the event that a decision to dismiss an editorial decision is the kind of action one dared speak against the arbitrary actions of Jack who always underestimate the ability of Maddy in guiding news event. “I'm so proud of you, Madeleine,” said a soft voice Phyllis Armstrong , wife of the president. “That was a very brave thing you did, and the editorial is very necessary. It was a wonderful broadcast, Maddy.” “Thank you, Mrs. Armstrong, said Maddy.” (Steel, chapt 3: 32) The quotation above shows that Maddy has strengtheness against Jack’s commands which acrosses with Maddy’s principle. She does not want to regard herself as victim of victimhood. Although Jack has stopped the program however Maddy is not afraid to air the program without unbeknownst by Jack. Without helping from Jack’s concepts, Maddy actually has power in delivering news well. It can be shown as many audiences and the president’s wife commend her broadcast is very amazing. For Maddy, the struggle which has done by her toward Janet is a form of struggle as woman to help other women and also her efforts to show her existence. In the sphere of work, Maddy does not want to regulated by Jack, she wanted to be given the opportunity to organize the editorial program which is ever hosted by her. 2.2 Doing action Liberal feminism supports that every women have equal rights and freedom same as men, including freedom in making choice for reproduction. As Maddy decides to marry with Jack, she thinks that her life will brings happiness. Jack always brings luxurious gifts for Maddy, she never got abuses physically like her marriage life with Bobby Joe and her childhood life that her father always beats her and his mother. However, Jack never gives rights as individual and social beings. One of human right violation which is perpetrated by Jack to Maddy is prohibitting Maddy to have a baby that Maddy must allow her tube of uterus tied in the name of love her for Jack. “Why didn't you tell me that you'd had a visit from my daughter?” Her eyes never lefthis as she asked the question, and she saw something cold and hard come into his, a burning ember that was rapidly being kindled by anger. “Why didn't you tell me you had a daughter?” he asked just as bluntly. “What I want to know from you is why you didn't tell me that you saw her. What were you saving it for?” (Steel, 111) The quotation above shows that as a woman, Maddy wants to her existence can be regarded, a form of recognition of the existence of women by men with giving woman to create reproduction choice. From the quotation above is explained that Maddy shows her anger to Jack as he has intended Maddy to meet her daughter who has ever regarded lost. The action of Jack to Maddy can be categorized with human rights violation to have descent. Understanding that Jack never accept Lizzy’s presence, Maddy does not care how Jack will respond the situation. In Maddy’s mind is only Lizzy. She deserves to have a right for having a child after Jack ever loss Maddy’s opportunity. As stated by Naomi Wolf that social equality is not things that are entreated from others. Women must be ready to have a place that has become their rights. Maddy realizes that she has a right to be mother without asking for permission from Jack, she still maintain her rights to regard Maddy to be her children and meets with her. The quotation can be seen below: “Where were you? Try telling me the truth this time.I was with Lizzie. Who is that?” My daughter. Oh, for God's sake,” he said.” (Steel, p.129). 2.3 Being Personal Autonomy “You owe me everything. And I hope you realize you'll be out of a job if you leave me.” His eyes glittered like steel.“Possibly. I'll let my lawyers handle that, Jack. I have a contract with the network.You can't just throw me out without notice or compensation.” She had gotten braver and smarter while fighting for her life in the rubble. (185) Based on the above text can be proved that maddy had dared to oppose, and to threaten Jack behind. The quotation above explains that the woman has power to determine self, body, and mind. Maddy has shows how she is able to stand alone. For sake of happiness and pleasure, she does not let his wife to hurt her heart agains. She deseves to find her autonomous choices witthout being afraid with threats from her husband as stated by John Stuart Mill above. After she decides to leave living which is borrowed by Jack, Maddy get offers to become a broadcaster of three big television station still she thinks that it is time for her taking care her daughter and her son first. She wants to feel how being a mother thrutfully as John Stuart Mill states that women have power to determine her self, her body, and her mind. In this case Maddy wants to determine her self as a mother first, “I don't know yet. I want to go back to work, but I want to enjoy you and Andy for a while. This is my first chance, and my last, to be a full-time mother. Her lawyer was organizing a major lawsuit against Jack and his network. He owed her a huge severance for kicking her out of her job, and there was the issue of slander, malicious intent, (Steel, p. 201). She also wants to determine her body as Madelaine Beaumont. Determining self, body, and mind according his or her own wishes without getting a force from other, it means that he or she has been personal autonomy. The quotation can be seen below: “She didn't want anything more to do with Jack Hunter. Even if she went on another show again, she had decided to do so as Madeleine Beaumont.” (Steel, p. 199) The quotation on 199-201 above can be explained that Maddy as an individual that has found her true identity as a woman, who ever had been despoiled by Jack, her husband. With the emergence of self confidence on Maddy cultivates an attitude of optimism in her mind that without abundant wealth from, happiness could be achieved by Maddy with is accompanied by her children. Maddy could choose to leave her husband, changes her name with using her own name and decides to work again without any coercion from others, she has personal autonomy, a autonomous decision making. Besides she has been personal autonomy, she also becomes a flourishing person that she still decides to work and she is not afraid to sue her husband and her husband networking as he had done violation toward Maddy’s name. CONCLUSION The first problem is domestic violence to woman reflected. Based on the result of data analysis and discussions which have been explained on previous chapter, it is revealed that in Journey happens oppression which is perpetrated by Jack to Maddy in their marriage life in some aspects, including emotional, sexual abuses then discrimination in sphere of work. Emotional abuse is reflected in Journey including humiliation, threatening, belittling, social isolation which is committed all by the main male character to the main female character. Meanwhile sexual abuse is reflected in Journey including prohibition to have a baby by the main male character, Jack to the main female character, Maddy, forces in having sex, use torturing sexually when having sex as a punishment so that the main female character is submissive with the main male character. Discrimination in working spheres also reflected in Journey including subordination toward integrity of woman, for instance woman is considered incapable of doing anything without the concept of men's, women in this novel is described only as a performer who does things her own unsubstantiated opinion, and woman is only regarded as an benefit asset in increasing television program which is guided by the main female character. Woman in Journey need only look beautiful in a career without having to use her mind and her ability as an independent individual. In Journey, the female character, Maddy is always prosecuted for looking beautiful, elegant and not much demand to her husband. Woman does not have important role in all of spheres such as in her private life at home and in her public life at working place. The second problem is how woman resists against violence. The forms of woman’s resistance which are reflected in Journey, including speak out action, act of courage to speak to her husband when finding things that are not in accordance with her conscience in addition to speak out, the main female character in Journey resists violence through doing action, against the rules which across with the principle of the main female character mind as the image of woman in Journey is reflected very dare to oppose rules which limit ability of woman in expression. As her husband still does not show change in attitude, finally the main female decides to become personal autonomy, dare to take a firm stance with which she considers leaving her husband and had trampled her dignity as a woman. In the field work, Maddy in an attempt to show her integrity dare express her opinions, and show the concept of the work which should become her responsibility. Besides she is brave to speak out, the main female character in attempt to get happiness she is brave to oppose all imposed restrictions by the main male character, Jack. Form of opposition is reflected in Journey is she keeps on airing the program of editorial, which has been banned by Jack. The main female character presents the editorial in an effort to gain public attention over the fate of other women, still socialization with her friends, and meets with her daughter although she gets refusal from her husband. Besides doing action, the female character chooses to be personal autonomy with leaving home in order to getting happiness in her life. She has successed in determining her self, her body, her thinking that she will be happy without her husband. The resistance of female character to her husband for leaving her husband is having arisen awareness in women that she can be independent in the material, social, and can decide for the direction and purpose of her life with the ability, intelligence, skills she has with supporting her friends, and her daughters. She wants to reach her dreams to achieve happiness without getting abuses, and being a mother for her daughter who is ever entrusted in baby house and a new baby whom she gets from her friend, find another men who can love her so much and understand her weakness or her excess. SUGGESTION From some of the conclusion above, the writer can propse following suggestions: a) Gender injustice can happen anytime and anywhere and overwrite both men and women in all aspects and levels of life. Therefore, there needs to be an effort to address gender inequality. b) There needs to be provision of an understanding of gender and gender inequality early on in the community both within the family, the education in school, and so forth. c) The result of this study is served as a material to conduct in-depth analysis of gender approach, especially gender inequalities that afflict women. REFERENCES Bhasin, Kamala (2000). Understanding Gender. New Delhi : Kali for Women Carter, David (2006). Literary Theory Pocket Essential. United States of America : Harpenden Denmark, Florence (2008). Psychology of Women. United States of America : Greenwood Publishing Group, Inc. Dustin, Ells Howes (2009). Toward a Credible Pacifism Violence and the Possibilitties of Politics. Albany : State University of New York Press. Humm, Maggie (1986). Feminist Criticism. Women as Contemporarary Critics. United States of America : The Harverster Press. Joda A, Zubairu H, Abdulwaheed S, Giwa A, Abass R, Adidu V, Okagbue I, Balogun O (2007). Against Violence Against Women. Baobab Legal Literacy Leaflet No.1 Khan, Mehr (2000). Domestic Violence Against Women And Girl : UNICEF Innocenti Digest Lundberg, Paula K and Shelly Marmion (2006). Intimate’’ Violence against Women : When Spouses, Partners, o Lovers Attack. United States of America: Greenwood Publishing Group, Inc. Margi, McCue Laird (2002). Domestic Violence : A Reference Handbook Contemporary World Issues. United States of America: ABC-CLIO. Tong, Rosemarie (2009). Feminist Thought. United States of America: Westview Press. Wolf, Naomi (1994). Fire With Fire, The New Female Power and How it Hill Chane the 21st Century. United States of America : Vintage. Wood, Julia T (2009). Gendered Lives Communication. Canada : Nelson Education, Ltd.